Penerapan Sistem Informasi Penerimaan Beasiswa KIP Kuliah Dengan Implementasi Simple Additive Weighting (SAW) : Studi Kasus Pada Universitas Muhammadiyah Prof. Dr. HAMKA - Muhammad Fathan Fauzan; Alfino Putra Laksana; Nur Chalik Azhar (Prosiding Seminar Nasional Teknoka, 2023)
This research explores the application of the Simple Additive Weighting (SAW) method in selecting KIP Lecture scholarship recipients at Muhammadiyah Prof. DR. HAMKA University (UHAMKA). The problem process is currently experiencing slowness and inaccuracy, prompting the need for a Decision Support System to increase accuracy and efficiency. With criteria adapted to UHAMKA policy, the aim of this research is to increase accuracy and reduce selection time. The SAW method is used to give weight to each alternative and this method can help the selection process be more accurate. This method produces efficient ranking of KIP Kuliah scholarship recipients. The results of tests carried out using black box testing show that the implementation of SAW can be efficient and effective. testing based on 2 examples of test cases showed that the SAW method. The accuracy results of the SAW method in case 1 were 100%, in case 2 it was 78% so that it could be used in determining prospective scholarship recipients at UHAMKA and make a positive contribution to student welfare and the image of the institution.